(3CUhd JQcjH GdCOhjIs - (3fLjH GdOjf eMeO Hf Ydj Hf YeQ, GdSeQbfOj,J (B619 (3g` s
(3ChdgG (B:s
(3GdMeO ddg bGd GdTjN eMeO Hf Ydi Hf YeQ GdSeQbfOi Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg s
(3BNQgG (B:s
(3efge ef jLeYgG eYkG , Ch jSJYedgG Ydi GdJYGbH ecQQkG Ch ZjQ ecQQ , hGdMeO ddg Mb MeOg s
(3hCdMb HBNQgGs
(3GdHGH GdKGef ef cJGH eaJGM GdWHs
(3dGHf gfOs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs